Professor, Dept. of Medical Beauty care, Jungwon University , 85 Munmu-ro, Goesan-eup, Goesan- gun Chungbuk, 367-700, Republic of Korea - Kim, Eun-Hee; Kim, Ah-Hyeon; Park, So-young; Shim, Youn-soo; Jeon, Eun-young; An, So- youn (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: To assess Korean oral health indices and compares these trends with those found for other OECD countries to determine their characteristics and causes.Methods/Statistical analysis: This retrospective study examined national data obtained from official epidemiological surveys carried out in Korea during 2000, 2003, 2006, 2010 and 2012. The studied units were Korean municipalities and their average DMFT index and average CPI values for children and adolescents.Findings: The estimated mean dft index (decayed and filled teeth) values in 5-year-old children were as follows:5.48 in 2000, 4.12 in 2003, 2.85 in 2006, 2.99 in 2010 and 2.79 in 2012. The estimated mean DMFT index valuesin 12-year-old children were as follows: 3.3 in 2000, 3.25 in 2003, 2.17 in 2006, 2.08 in 2010 and 1.84 in 2012. The ratio of the CPI code 0 repeatedly increased and decreased from 46.29% in 2000. The number for sealants used in 8-, 12- and 15-year-olds was 0.48, 0.42, and 0.29, respectively, in 2000 and 1.82, 2.36, and 2.12,respectively, in 2012. Improvements/Applications: For children aged 12, the CPI rate for code 0 increased, gingival bleeding on probing decreased, and the level of calculus did not change between 2000 and 2012. The average number of sealed teeth increased continuously by approximately 4- to 7-fold over 12 years.